Prooxidant mechanisms of selenium toxicity – a review - Mézes, Miklós; Balogh, Krisztián (Acta Biologica Szegediensis, 2009)
Selenium is an essential trace element in living organisms as integral part of seleno-enzymes. However, excess amount of selenium is toxic for so-called non-accumulator plants, animals and humans. The toxicity for plants depends on the capacity of synthesis of non-protein amino acids and also their volatilization in the form of dimethylselenide, while in animals on the rate of methylation and its excretion. In vitro studies showed that there are selenium-resistant animal and human cell lines which showed altered selenium uptake. Exact mechanism of selenium toxicity remains unclear but there are many data about its prooxidant effect particularly in the form of selenite, while selenomethionine and selenocysteine are less toxic. Inorganic forms of selenium reacts with tissue thiols, such as glutathione to form seleno-trisulphides and those are reacting with other thiols to generate oxygen free radicals, such as superoxide anion. Organic diselenides are converted into selenols in presence of thiols which also results oxygen free radical generation. Another free radical hypothesis of selenium toxicosis is based on the methyl-selenide formation, which also results superoxide radicals and induce oxidative stress. Besides free radical formation selenium can have inhibitory effects on thiol proteins, for instance those which have antioxidant affect.